2003
DOI: 10.1002/j.1939-4640.2003.tb02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosome Deletions in Azoospermic Men in India

Abstract: Genetic factors cause about 10% of male infertility. Azoospermia factors (AZFa, AZFb, AZFc) are considered to be the most important for spermatogenesis. We therefore made an attempt to evaluate the genetic cause of azoospermia, Y chromosome deletion in particular, in Indian men. We have analyzed a total of 570 men, including 340 azoospermic men and 230 normal control subjects. DNA samples were initially screened with 30 sequence-tagged site (STS) markers representing AZF regions (AZFa, AZFb, AZFc). Samples, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 45 publications
7
62
1
Order By: Relevance
“…66.6% AZFc deletions amongst the cases with AZF deletions, as seen for both population groups, is in agreement with the reports of Hopps et al (2003). However, Thangaraj et al (2003) reported high incidence of 82.8%. McElreavey et al (2000) have observed that deletions involving the AZFc region are the most frequent amongst all the AZF deletions.…”
Section: Azf Deletionssupporting
confidence: 90%
See 1 more Smart Citation
“…66.6% AZFc deletions amongst the cases with AZF deletions, as seen for both population groups, is in agreement with the reports of Hopps et al (2003). However, Thangaraj et al (2003) reported high incidence of 82.8%. McElreavey et al (2000) have observed that deletions involving the AZFc region are the most frequent amongst all the AZF deletions.…”
Section: Azf Deletionssupporting
confidence: 90%
“…Concurrent to these, OkutmanEmonts et al (2004) and Machatkova et al (2003) also did not find any AZFa deletion among their 71 Turkish and 198 Czech cases, respectively. Least frequencies of AZFa deletions among azoospermic men have been reported among Russians (Loginova et al 2003), Chinese (Yang et al 2003), North Americans (Hopps et al 2003), Indians (Thangaraj et al 2003) and Japanese (Kihaile et al 2005).…”
Section: Azf Deletionsmentioning
confidence: 97%
“…The reason is probably the strict selection criteria applied in our study as well as geographic and ethnic differences. Within India, studies have been carried out in different regions, which showed a frequency between 5% and 9.5% (21)(22)(23). The selection criteria in these were also different from the criteria used in our study, the number of STSs used were variable.…”
Section: Discussionmentioning
confidence: 68%
“…No consensus has yet been reached about the optimal number of STSs that should be used, or the specific loci that should be imperatively screened (Choe et al, 2007). Some authors have suggested that using more sets of primers increases the chances of detecting microdeletions (Thangaraj et al, 2003;Mitra et al, 2006). On the other hand, other studies have shown that the prevalence of microdeletions detected did not increase with increasing numbers of STSs used (Choe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%